CLINICAL AUDIT OF DIAGNOSTIC RESULTS FROM PERINATAL AUTOPSY. (February 2015) - Patton, Kirralee; Jevon, Gareth
Abstract : Aim: To assess the contribution of the perinatal autopsy to the diagnosis and investigation of fetal and placental disease in an era of advanced prenatal ultrasound and molecular diagnostic techniques. Method: This is a 1 year retrospective study that reviewed all autopsy results from fetuses of 20 weeks gestation and above, for diagnostic information and data regarding fetal or placental findings. All autopsies were performed at the sole tertiary perinatal pathology centre for Western Australia. Where available, autopsy findings were correlated with ultrasound and genetics. Results: 147 autopsies from fetuses above 20 weeks gestation were performed during this period. One coronial case was not reviewed. Six cases had known chromosomal abnormalities. Of the remaining 140 autopsies, 125 (89%) reported abnormal findings and 101 (81%) of these provided additional information regarding the fetus or placenta. Fetal or placental pathology was not identified in only eight (6%) cases and seven (5%) of cases were of uncertain clinical significance. Discussion: Despite significant advances in prenatal ultrasound and molecular diagnostic techniques, defining the cause of perinatal disease is challenging. Autopsy continues to be the gold standard for the investigation of perinatal disease, providing the opportunity to confirm diagnosis, find additional malformations or changing and broadening the range of diagnosis of perinatal pathology.